Seismic vulnerability assessment of elevated water tanks with variable staging pattern incorporating the fluid-structure interaction. (December 2021) - Mohammad Mansour, Ayman; Kassem, Moustafa Moufid; Mohamed Nazri, Fadzli
Abstract: The damage suffered by elevated water tanks in previous seismic events can be generally attributed to poor performance of their frame-type supporting structure. It is pivotal to quantify the damage experienced by these tanks in damage states in order to ascertain their performance. In this study, the nonlinear response of frame-supported elevated water tanks is investigated using performance-based earthquake engineering method by utilizing the top drift of frame staging as the engineering demand parameter to evaluate its performance level. The influence of different patterns of reinforced concrete frame staging on the response of elevated water tanks was quantified using a fragility assessment. Finite element approach was employed and a total of nine models were developed representing the variation in staging patterns (basic, cross, and radial bracing configurations) and water-filling levels (empty, half-full, and full conditions) of the tanks and considering the fluid–structure interaction effect. Non-linear analyses were performed based on different seismic scenarios, and the seismic damage states from each staging pattern were evaluated. Fragility curves were generated according to three performance limit states specified in Vision 2000 and based on incremental dynamic analysis results for each staging pattern. Finally, the collapse margin ratios were quantified to evaluate the seismic safety margin against collapse of the elevated water tanks. From the analysis results, elevated water tanks having staging with cross and radial configurations showed better seismic performance compared to the basic configuration.